2019
DOI: 10.1177/1010428319826853
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA-1290 as a potential biomarker for response to chemoradiotherapy and prognosis of patients with advanced oral squamous cell carcinoma: A single-center retrospective study

Abstract: MicroRNAs are a class of small, endogenous, noncoding 18-to 24-nucleotide-long RNAs that can regulate multiple processes related to cancer progression. However, their clinical value in patients with oral squamous cell carcinoma has not yet been fully explored. Therefore, the aim of this study was to investigate the clinical significance of circulating microRNAs in oral squamous cell carcinoma patients. The expression levels of circulating miR-1246 and miR-1290 in healthy volunteers and oral squamous cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Furthermore, research observations indicated that, miR-1290 can behave as non-invasive biomarkers that could be used as early detection, prognostic and diagnostic biomarker for broad spectrum of cancers (Mo et al, 2015;Kobayashi et al, 2018). In case of oral cancer, Nakashima et al found that miR-1290 expression level was significantly lower in the plasma of oral squamous cell carcinoma patients than in that of healthy, however, circulating miR-1290 status suggested as useful biomarker to predict the clinical response to chemoradiotherapy as well as overall survival in oral squamous cell carcinoma patients (Nakashima et al, 2019). As we found that most of hub genes (including CD44, ACLY, ACTR3, STAT1, LAMC2 and YWHAZ) were potentially targeted by has-miR-5580-3p, it indicates that this miRNA might play a key role in OSCC.…”
Section: A) B)mentioning
confidence: 99%
“…Furthermore, research observations indicated that, miR-1290 can behave as non-invasive biomarkers that could be used as early detection, prognostic and diagnostic biomarker for broad spectrum of cancers (Mo et al, 2015;Kobayashi et al, 2018). In case of oral cancer, Nakashima et al found that miR-1290 expression level was significantly lower in the plasma of oral squamous cell carcinoma patients than in that of healthy, however, circulating miR-1290 status suggested as useful biomarker to predict the clinical response to chemoradiotherapy as well as overall survival in oral squamous cell carcinoma patients (Nakashima et al, 2019). As we found that most of hub genes (including CD44, ACLY, ACTR3, STAT1, LAMC2 and YWHAZ) were potentially targeted by has-miR-5580-3p, it indicates that this miRNA might play a key role in OSCC.…”
Section: A) B)mentioning
confidence: 99%
“…Ling Ye et al discovered that tissue miR-1290 expression levels were positively correlated with the dMMR status and predicted the prognosis of patients with CRC receiving 5-FU treatment [ 32 ]. The circulating miR-1290 level was also a potential biomarker for the response of patients with advanced oral squamous cell cancer to 5-FU-based chemoradiotherapy [ 33 ]. Therefore, the relationship between circulating miR-1290 expression and chemotherapy resistance in patients with gastrointestinal tumors is worthy further study.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miR-1290 was also a potential biomarker for response to 5-FU-based chemoradiotherapy of patients with advanced oral squamous cell cancer [30]. Therefore, the relationship between circulating miR-1290 expression and chemotherapy resistance in gastrointestinal tumors is worthy of study.…”
Section: Discussionmentioning
confidence: 99%